PERPUSTAKAAN DIGITAL SEBAGAI PENUNJANG PEMBELAJARAN JARAK JAUH - Ramdanil Mubarok (Al-Rabwah, 2021)
This paper aims to describe the role of digital libraries as support for distance learning during a pandemic. This research uses the type of literature study conducted to prepare a research framework and make use of general literature sources to obtain research data. The stages of research carried out in this library research are determining the topics to be studied, searching for and selecting data by the focus of the study, conducting source analysis, and developing data by the focus of the research and concluding it. The result is that the library as a support and learning resource must adapt to distance learning patterns so that libraries that were originally only a pile of books and are still traditional have to change their service patterns to a digital library model so that it makes it easier for users to take advantage of the library during the Covid-19 pandemic. To maximize the role of digital libraries, students must also actively increase their learning independence and must have awareness of students and the role of parents in directing, helping, guiding, and motivating students so that good collaboration between students and parents can be created. and teachers in optimizing the role of digital libraries in distance learning. Thus it will create a reading habit for students from their awareness and will further increase the effectiveness of learning at distance during the Covid-19 pandemic.